An Image-Based Captcha System Using Click - Mahdin, Hairulnizam; Azmi, Mohd Sanusi; Kasim, Shahreen; Ridzuan, Farah Ruzanna (Zibeline International, 2019)
CAPTCHA stand for “Completely Automated Public Turing test to tell Computers and Humans Apart”. It is a technique of testing where only human can solve it and computer-generated system (bots) could not get through it. In this paper, a new type CAPTCHA system is proposed. The proposed scheme named ClickShape, developed by using a technique based on image-based CAPTCHA. ClickShape will ask user to click on the shape displayed by the system. It is quite similar to image-based CAPTCHA where user have to choose any specific image, for example image of a signboard. As for this captcha image of a shape is easier to be recognize by human. This type of CAPTCHA had developed by using HTML, JavaScript, PHP and Cascading Style Sheets (CSS).